2019
DOI: 10.3389/fncel.2019.00040
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Depletion Regulates Axonal Growth and Enhances Central and Peripheral Nerve Regeneration

Abstract: Axonal growth during normal development and axonal regeneration rely on the action of many receptor signaling systems and complexes, most of them located in specialized raft membrane microdomains with a precise lipid composition. Cholesterol is a component of membrane rafts and the integrity of these structures depends on the concentrations present of this compound. Here we explored the effect of cholesterol depletion in both developing neurons and regenerating axons. First, we show that cholesterol depletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 50 publications
1
36
1
Order By: Relevance
“…Supporting this hypothesis, Amsalem, Poilbout, Ferracci, Delmas, and Padilla () demonstrated how inflammation lowers the cholesterol content in DRG neuron cultures and that pharmacological depletion of neuronal cholesterol causes sensitization of nociceptive neurons, promoting mechanical and thermal hyperalgesia by activation of voltage‐gated Nav1.9 channels. Furthermore, it was recently described how depletion of cholesterol promotes growth in developing neurons and increases axonal regeneration in the peripheral nervous systems (Roselló‐Busquets et al, ). It may, therefore, be speculated that reduced cholesterol synthesis by SGC contributes to lowering cholesterol levels in injured sensory neurons with the purpose of promoting neuronal repair and axonal regeneration, however at the cost of increasing nociceptive activity.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this hypothesis, Amsalem, Poilbout, Ferracci, Delmas, and Padilla () demonstrated how inflammation lowers the cholesterol content in DRG neuron cultures and that pharmacological depletion of neuronal cholesterol causes sensitization of nociceptive neurons, promoting mechanical and thermal hyperalgesia by activation of voltage‐gated Nav1.9 channels. Furthermore, it was recently described how depletion of cholesterol promotes growth in developing neurons and increases axonal regeneration in the peripheral nervous systems (Roselló‐Busquets et al, ). It may, therefore, be speculated that reduced cholesterol synthesis by SGC contributes to lowering cholesterol levels in injured sensory neurons with the purpose of promoting neuronal repair and axonal regeneration, however at the cost of increasing nociceptive activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous results showed that Nystatin increases axon regeneration post-axotomy in primary cell cultures of hippocampal neurons (Roselló-Busquets et al, 2019). The ability of axons to regenerate is lost in adult CNS neurons (He and Jin, 2016;Curcio and Bradke, 2018;Fawcett, 2019).…”
Section: Nystatin Increases Axon Regeneration In Immature and Differementioning
confidence: 95%
“…Consistent with the lack of action on NO production, the effect of highest doses of Nystatin (10 µM and 25 µM) on growth cone area and filopodia density is independent of NOS inhibition (Figures 6E-H). Methyl-betacyclodextrin (MβCD) is a compound that, similar to Nystatin, extracts cholesterol from cell membranes, increasing growth cone area and filopodia number (Roselló-Busquets et al, 2019).…”
Section: Nystatin Increases the Growth Cone Area And Filopodia Densitmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, some studies have also reported different ways to lesion axons on lab-on-chip devices (i.e., [7]). However, these studies mainly used the devices to support in vivo experimentation and did not take advantage of the full potential of these platforms (see [8] for a recent example). Concerning PN-modelling, several methods were developed to generate contractile myotubes on lab-on-chip devices (i.e., [9][10][11]).…”
Section: Introductionmentioning
confidence: 99%